Effect Of Replacement Of Maize By Animal-Fat On Growth And Feed Conversion Efficiency In Large White Yorkshire Pigs (Applied Biological Research, 2020)
An experiment was conducted to assess the effect of replacement of maize  by animal-fat on the growth and feed conversion efficiency in Large White  Yorkshire pigs. Thirty weaned piglets were randomly divided into three  groups and allotted to the three dietary treatments [control ration (as per  NRC, 1998), 50% maize of control ration replaced by animal-fat and 100%  maize of control ration replaced by animal-fat] and maintained for 70 days.  The daily feed intake and fortnightly body weight were recorded and  average daily gain and feed conversion efficiency calculated. The average  daily gain and feed conversion efficiency were found to be 813.0, 769.8, 678.4 g and 2.80, 2.88, 3.08, respectively, for the three respective treatment groups.  There was no significant difference in the performance of pigs belonging to  control ration group and the group fed with 50% maize of control ration  replaced by animal-fat, but 50% replacement had higher average daily gain  and feed conversion efficiency than the group fed with 100% maize of control ration replaced by animal-fat. The study revealed that the pigs fed  diet having 50% maize replaced by animal-fat performed in a similar way  to that of control fed group and was better than those pigs fed diet with  100% replacement of maize by animal-fat.
Keywords: Animal fat; eed conversion efficiency; growth; maize; pigs